Biografia no ensino de História : trajetória de Mahommah Gardo Baquaqua no estudo da diáspora africana - Lima, Edneia Xavier de (2020)
The historical formation of the current Brazilian population took place through a long process of interaction between peoples of America, Europe and Africa, marked by constant relations of conflicts and interests. Much of the peoples of Africa, for example, were brought mainly to America in a long diasporic movement, whose massive and forced displacements across the Atlantic ocean served the lucrative slave trade. The individual trajectories about the people brought and enslaved are little or not known and studied in the school environment, predominant generic approaches and sometimes, of passive people. In this sense, how is it possible to highlight the protagonisms? In the last decades, many historians have invested in the biographical genre as a source for historiographical production, for dealing with the particularities and especially for rescuing the life stories of ordinary people and little seen. With a renewed perspective, the biography enriches views and understanding of different societies and times, because it considers the singularities of everyday life and the role of people. The present research aims to present an alternative methodology for the use of this source in history classes with high school students, contemplating the study of the African diaspora in Atlantic relations. The experiences of Mahommah Gardo Baquaqua contribute to this study, character who stood out for leaving an autobiography, published in the United States in 1854, in which he reports the context of his time, crossing the different spaces in which he worked. Brought from West Africa, region where he was born, addresses aspects of the culture of its people. In America, brought to be enslaved, acted beyond the expectations imposed, resisting in several ways to reaffirm the freedom that was within you; after passing through Brazil, the United States and Haiti, he arrived in England, place where he looked for ways to return to his people. In his writing, Baquaqua exhibited his conceptions, yearningsm joys, sorrows, pains and hopes, feelings for which 21st century students also live in their daily lives, but in another context. To carry out this proposal, the resulto of this research will be a Didactic Sequence and will serve as a didactic support for the approaches.